Language and text data, models, information and applications - Pawłowski, Adam; Mačutek, Ján; Embleton, Sheila M.; Mikros, George K., 1969- (Amsterdam studies in the theory and history of linguistic science. Current issues in linguistic theory ;, 2021)
"Specialists in quantitative linguistics the world over have recourse to a solid and universal methodology. These days, their methods and mathematical models must also respond to new communication phenomena and the flood of data produced daily. While various disciplines (computer science, media science) have different ways of processing this onslaught of information, the linguistic approach is arguably the most relevant and effective. This book includes recent results from many renowned contemporary practitioners in the field. Our target audiences are academics, researchers, graduate students, and others involved in linguistics, digital humanities, and applied mathematics"--